The Strategies and Barriers of the Implementation Qanun Khalwat to Prevent Misbehaviorous of Banda Aceh Adolescent - Abubakar Abubakar; Anwar Anwar (JURNAL SERAMBI ILMU, 2011)
Although the Syariat Islam have taken place more teen years, fenomenally the adolescence’s behavior during this time do not change according to Syariat Islam, even its indication to be warry, such as same adolescence’s case which was found latly as narkoba till freesex, that case has be able to catagorized as juveneli deliquence, similarly the report of Dinas Syariat Islam Aceh Province in 2009 it has accured the increasement of khalwat violation significanly. In Banda Aceh 2006 there where 132 cases (42 heavy cases, 96 light cases), in 2007 there were 149 cases (47 heavy cases, 102 light cases) in 2008 there were 103 cases (22 heavy cases, 77 light cases) in 2009 there were 91 cases (21 heavy cases, 70 light cases) and last one untill Pebruari 2010 there were 3 cases of heavy khalwat, of the whole cases wich was found most of the actor were the adolescence. The result of data processing was found more violation of khalwat by the adolesencence as level as university students showed data wich more woory, for example SMA students of Banda Aceh have done freesex 6,42%, while students of university 12,02%. This indication show that that adulesecence of Banda Aceh have done the heavy violation of Qanun Khalwat/Meusum. This cases is adopt to Dinas Kesehatan dan Unicef finding that 10% of PSK in Aceh were university students. There for several strategies could covered to optimalize the implimentation of Qanun Khalwat, among athers : the development of a village structure proportionally, the village structure which has been existed during this time having five Kaur, namely Kaur Pemerintahan, Kaur Pembangunan, Kaur Keuangan and Kaur umun and Kesra. It is nacessery to add one more kaur that is Kaur Syariat Islam, That kaur should be lead by its figure arising from each village which posses various criterian suited to characteristic of their duties, the adition of Kaur Syariat Islam could be concentrated especially to the village that has done more violation. It is also neseeary to make a working contract with owners of the hostles, renting houses, hotels, guest houses, cafetarias, barber shops/saloon, warnet, warmang and athers concerning their consistence of implimenting and keeping Syariat Islam in their regions, As it was implied in Qanun No. 5 Syariat Islam and Qanun No. 14 about Khalwat especially section 6 and 7 a long with section 25, verses a and b. It is essencial to exist a good team work with various elements in the community, it is importent to guid them especially to the adulesence either to the adulesence as level as senior higt shcool or university, because 70% of the adolesecences at the stage of education institution mentioned have done misbehaviour. The responsibility iis only as suggestions during this time so, for the next time, this could formed to be more light or binding and posses sanction for the leader if he makes violations, even, it is begins from administrative sanction to taking out of a legalization letter. The sunction given during this time is not serious, the comporation of giving sunction do not refer to violation of Qanun Khalwat and Syariat Islam but it is more tendency to the comporation of economics, so, the implimentation of Syariat Islam at the institution always become a problem. There were not a legalization of Qanun Jinayat, actually WH do not have exsisted a formal legalization in making succesful the implementation of Syariat Islam, therefore, it is important to privide a law umbrella that more adequate to impliment Syariat Islam completly, begining from catching, BAP, till to the Court, most of the part of the cases have been provide in Rancangan Qanun Jinayat Syariat Islam in 2009, that written in 22 chapter and 253 sections, neverlees untill now, it is not legalized by a Aceh Governor without real reasons.